The prevalence of microalbuminuria and relevant cardiovascular risk factors in Turkish hypertensive patients - (:unkn) unknown (My University, 2011)
Objectives: A growing body of data illustrates the importance of microalbuminuria (MAU) as a strong predictor of cardiovascular risk in the hypertensive population. The present study was designed to define the prevalence of MAU and associated cardiovascular risk factors among Turkish hypertensive outpatients. Study design: Representing the Turkish arm of the multinational i-SEARCH study involving 1,750 sites in 26 countries around the world, a total of 1,926 hypertensive patients from different centers were included in this observational and cross-sectional survey study. Patients with reasons for a false-positive MAU test were excluded. The prevalence of MAU was assessed using a dipstick test, and patients were inquired about comorbidities, comedication, and known cardiovascular risk factors. Results: The overall prevalence of MAU was 64.7% and there was no difference between genders. Most of the patients (82.5%) had uncontrolled hypertension, 35.6% had dyslipidemia, and 35.5% had diabetes, predominantly type 2. Almost one-third of the patients (26.4%) had at least one cardiovascular-related comorbidity, with 20.3% having documented coronary artery disease (CAD). Almost all patients (96.8%) had one or more risk factors for cardiovascular disease in addition to hypertension, including family history of myocardial infarction or CAD, diabetes, dyslipidemia, lack of physical exercise, and smoking. A trend towards higher MAU values in the presence of CAD was determined. Conclusion: Microalbuminuria tests should be routinely used as a screening and monitoring tool for the assessment of subsequent cardiovascular morbidity and mortality among hypertensive patients. © 2011 Turkish Society of Cardiology.
Keywords: Albuminuria/complications/epidemiology; Cardiovascular diseases; Coronary artery disease; Hypertension/complications; Prevalence; Risk factors; Turkey/epidemiology